2000
DOI: 10.1054/bjoc.1999.0974
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic aspects of the cytotoxic activity of glufosfamide, a new tumour therapeutic agent

Abstract: β- D -Glucosyl-ifosfamide mustard (D 19575, glc-IPM, INN = glufosfamide) is a new agent for cancer chemotherapy. Its mode of action, which is only partly understood, was investigated at the DNA level. In the breast carcinoma cell line MCF7 glufosfamide inhibited both the synthesis of DNA and protein in a dose-dependent manner, as shown by the decreased incorporation of [3H-methyl]-thymidine into DNA and [14C]-methionine into protein of these cells. Treatment of MCF7 cells with 50 μM glufosfamide was sufficient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
27
0
1

Year Published

2002
2002
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 10 publications
(14 reference statements)
0
27
0
1
Order By: Relevance
“…The cell line CL-V5B is *30-fold more sensitive (based on D 10 values) than the parental 'wild-type' cell line to the cytotoxic effect of b-D-Glc-IPM, as measured by loss of colony-forming ability of the cells (Seker et al, 2000 and Figure 1). To see whether this hypersensitivity is due to the induction of apoptosis and/or necrosis, both endpoints were measured in parallel by annexin V and propidium iodide double-staining and flow cytometry as previously described (Ochs and Kaina, 2000).…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…The cell line CL-V5B is *30-fold more sensitive (based on D 10 values) than the parental 'wild-type' cell line to the cytotoxic effect of b-D-Glc-IPM, as measured by loss of colony-forming ability of the cells (Seker et al, 2000 and Figure 1). To see whether this hypersensitivity is due to the induction of apoptosis and/or necrosis, both endpoints were measured in parallel by annexin V and propidium iodide double-staining and flow cytometry as previously described (Ochs and Kaina, 2000).…”
Section: Resultsmentioning
confidence: 98%
“…Once inside the cell the drug is cleaved preferentially by intracellular glucosidases to form the ultimate cytostatic drug ifosfamide mustard (Seker et al, 1996). It has previously been shown that treatment of MCF-7 cells with b-D-Glc-IPM leads to activation of poly(ADP-ribose) polymerase (Seker et al, 2000). In the same study, by using an in vivo model system consisting of isogenic cell lines deficient and proficient for either O 6 -methylguanine-DNA methyltransferase (MGMT) or crosslink repair, it could be demonstrated that the most critical cytotoxic lesions caused by b-D-Glc-IPM are very likely to be DNA crosslinks (Seker et al, 2000).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This compound has been tested for its therapeutic activity against head and neck cancer, pancreatic adenocarcinoma, and non-small-cell lung cancer (Briasoulis et al, 2003;Dollner et al, 2004;Giaccone et al, 2004). Glufosfamide represent a novel oxazaphosphorine analog that uses the glucose transporter system for cellular entry to damage nuclear DNA (Seker et al, 2000).…”
Section: -Aminonicotinamidementioning
confidence: 99%
“…Using an immuno chemical approach, Rosenthal et al (1998) Hinshaw et al (1999) analyzed PAR formation in permeabilized endothelial cells and keratinocytes upon treatment with 250 and 500 mM of SM for 2, 3, and 5 h, showing a 2 4 fold increase in signal intensities (Hinshaw et al, 1999). Using fluorescence microscopy, Seker et al (2000) showed PAR formation in MCF7 cells 24 h after glufosfamide treatment (50 750 mM). Using biotinylated NAD + in an ELISA approach, Kehe et al assessed PAR formation in permeabilzed HaCaT cells upon pulse treatment of cells for 30 min with 10 1000 mM SM followed by further incubation of cells for 45 min in SM free medium leading to a maximum four fold increase in signal intensities (Kehe et al, 2008).…”
Section: Introductionmentioning
confidence: 99%